Analysis of the Value of Character Education in Arleen Alexandra's Fairy Tale I am a Great Leader and Its Relevance as a Learning Support Book for Elementary School Students - Arina Safaatul Chusna; Joko Purwanto; Rintis Rizkia Pangestika (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
This study aims to (1) analyze the intrinsic elements in Arleen Alexandra's fairy tale I am a great leader, (2) the value of character education in Arleen Alexandra's fairy tale I am a great leader, (3) the relevance of Arleen Alexandra's fairy tale I am a great leader as a learning support for elementary school students. This type of research uses descriptive qualitative research. The object used in this study was the fairy tale book I am the Great Leader by Arleen Alexandra. This research focused on the educational value of character education contained in Arleen Alexandra's fairy tale I am a great leader and its relevance as a supporting book for elementary school students' learning. The data source is a collection of fairy tales, fairy tale quotes. The research instruments used in this study are data recording cards containing narratives and conversations used in this study are Data logging cards that contain narrations and conversations that are fairy tale quotes. Data collection in this study was carried out using library techniques, reading techniques, and recording techniques. In data analysis techniques, content analysis (contect analysis) is used. The results of the analysis in this study can be concluded that (1) the intrinsic elements of the fairy tale I am the great leader of Arleen Alexandra's jarya consist of: (a) themes, (b) characters and characterizations, (c) plot, (d) setting, (e) point of view, (f) message. (2) the value of character education in Arleen Alexandra's fairy tale I am a great leader, namely: honest, tolerance, hard work, creative, independent, curiosity, respect for achievement, friendly or communicative, peace-loving, social care, responsibility. (3) The fairy tale book I am a great leader by Arleen Alexandra is relevant to be used as a learning support book for elementary school students, namely: sentence length and vocabulary in accordance with the reasoning power and reading ability of students, themed friendship, health and other themes that are relevant to the age and daily experience of students, in accordance with the interests and hobbies of students,  In accordance with morals and religion that is conveyed without patronizing, the structure of written language (spelling, grammar, cohence) is correct, which is presented variously (through rhyming words, poetry and dialogue) that is easy to understand, the information in the book does not harass any particular group of people.